The Position Of Bahasa Mandailing Within The Linguistic Affiliation Of Nusantara Languages: A Systematic Literature Review - Batubara, Muhammad Hasyimsyah (Program Studi Pendidikan Sejarah - Universitas Samudra, 2025)
The study of language kinship is a fundamental aspect of historical linguistics that aims to understand the genealogical relationships between existing languages. This study focuses on the Mandailing language, one of the regional languages in Indonesia that is included in the Austronesian family, to map existing literature on the kinship of the Mandailing language through a systematic literature review approach. The research method involves data analysis from databases such as Semantic Scholar and Google Scholar, with the inclusion criteria of articles published between 2015 and 2025 in Indonesian or English and discussing topics related to the Mandailing language and language kinship. The study results show that the Mandailing language is closely linked with other Batak languages, such as Toba Batak, Angkola, and Karo, and has deep Austronesian roots. This study reveals that although the Mandailing language has undergone significant phonological and morphological changes, it still maintains its characteristics as part of the Austronesian language family. In addition, this study also identifies the influence of Malay on Mandailing and the importance of this language in shaping the cultural identity of the Mandailing people. The conclusion of this study emphasizes the importance of efforts to preserve and document the Mandailing language to ensure its sustainability in the future. This systematic review of the literature provides a comprehensive overview of the research map related to the kinship of the Mandailing language and makes a real contribution to understanding the dynamics of language in Indonesia. This study also opens up opportunities for further studies, especially in sociolinguistic and interdisciplinary aspects, to reveal these linguistic findings' historical and anthropological significance.